Two Sides of Meaning: The Scalp-Recorded N400 Reflects Distinct Contributions from the Cerebral Hemispheres - Wlotko, Edward W.; Federmeier, Kara D. (Frontiers in Psychology, 2013)
The N400, a component of the event-related potential (ERP) associated with the processing of meaning, is sensitive to a wide array of lexico-semantic, sentence-level, and discourse-level manipulations across modalities. In sentence contexts, N400 amplitude varies inversely and nearly linearly with the predictability of a word in its context. However, recent theories and empirical evidence from studies employing the visual half-field technique (to selectively bias processing to one cerebral hemisphere) suggest that the two hemispheres use sentence context information in different ways. Thus, each hemisphere may not respond to manipulations of contextual predictability in an equivalent manner. This possibility was investigated by recording ERPs while presenting (in the left and right visual fields) sentence-final words that varied over the full range of sentence-level predictability. Right visual field/left hemisphere items were facilitated (as evidenced by reduced N400 amplitudes) over a broader range of predictability compared with left visual field/right hemisphere items, although both strongly predictable and completely unexpected items evoked similar responses in each visual field/hemisphere. Further, the pattern of N400 amplitudes over the full range of predictability significantly differed from a linear response function for both visual fields/hemispheres. This suggests that the N400 response recorded with standard central field presentation comprises different contributions from both cerebral hemispheres, neither of which on its own is sensitive to contextual predictability in an evenly graded manner. These data challenge the notion of a singular or unitary mode of comprehension and instead support the view that the left and right hemispheres instantiate unique, complementary language comprehension architectures in parallel.